2021
DOI: 10.18632/aging.203467
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between gray matter and white matter neurodegeneration in subjective cognitive decline

Abstract: Aims: To investigate the interplay between gray matter (GM) and white matter (WM) neurodegeneration in subjective cognitive decline (SCD), including thickness across the whole cortical mantle, hippocampal volume, and integrity across the whole WM. Methods: We included 225 cognitively unimpaired individuals from a community-based cohort. Subjective cognitive complaints were assessed through 9 questions covering amnestic and non-amnestic cognitive domains. In our cohort, 123 individuals endorsed from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 70 publications
0
8
0
1
Order By: Relevance
“…Several mechanisms may account for the link between walking speed and the risk of poorer cognitive function and slightly faster cognitive decline. First, neurodegeneration not only contributes to cognitive decline ( Cedres et al, 2021 ) but also to some extent affects walking abilities ( Tian et al, 2016 ). Some evidence has indicated that slow walking speed was associated with higher levels of amyloid β in key brain areas( Del Campo et al, 2016 ) as well as the changes in subcortical white matter and cortical gray matter volumes ( Holtzer et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms may account for the link between walking speed and the risk of poorer cognitive function and slightly faster cognitive decline. First, neurodegeneration not only contributes to cognitive decline ( Cedres et al, 2021 ) but also to some extent affects walking abilities ( Tian et al, 2016 ). Some evidence has indicated that slow walking speed was associated with higher levels of amyloid β in key brain areas( Del Campo et al, 2016 ) as well as the changes in subcortical white matter and cortical gray matter volumes ( Holtzer et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of association between SCD and objective olfaction, while present in the SCD + SOI group, might point to different underlying pathologies for each subgroup. In this population-based cohort, we hypothesized that the exclusive SCD presentation might represent an underlying subclinical pathology, presumably from a vascular origin ( Cedres et al, 2019 ; Diaz-Galvan, Cedres, et al, 2021 ), while the joint SCD + SOI group might be subclinically associated with other pathologies more strongly linked to olfaction, such as AD ( Duff et al, 2002 ) or Parkinson’s disease ( Doty, 2012 ). We base this speculation on the finding that SCD in the general population is associated with underlying cerebrovascular pathology ( Cedres et al, 2019 ; Diaz-Galvan, Cedres, et al, 2021 ) and an increased likelihood of progression to vascular dementia ( Slot, Sikkes, Berkhof, Brodaty, van der Flier, et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this population-based cohort, we hypothesized that the exclusive SCD presentation might represent an underlying subclinical pathology, presumably from a vascular origin ( Cedres et al, 2019 ; Diaz-Galvan, Cedres, et al, 2021 ), while the joint SCD + SOI group might be subclinically associated with other pathologies more strongly linked to olfaction, such as AD ( Duff et al, 2002 ) or Parkinson’s disease ( Doty, 2012 ). We base this speculation on the finding that SCD in the general population is associated with underlying cerebrovascular pathology ( Cedres et al, 2019 ; Diaz-Galvan, Cedres, et al, 2021 ) and an increased likelihood of progression to vascular dementia ( Slot, Sikkes, Berkhof, Brodaty, van der Flier, et al, 2019 ). Individuals with vascular dementia rarely present olfactory deficits ( Duff et al, 2002 ), since the symptomatology is highly dependent on where the vascular lesions are located ( Alves et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…R2 was computed to assess the quality of the RF models. Although aging is associated with WM neurodegeneration and greater WML volumes, 4 , 31 age was not included as a covariate in the models because it was controlled from the design (i.e., all participants were aged 70 years). For completeness of information, we also report Pearson correlation coefficients among the predictor variables included in the RF models and independent sample t tests for categorical variables that resulted important in the RF analysis.…”
Section: Methodsmentioning
confidence: 99%